A Translation of Song Lyric ‘Ignore’ by Emma Heesters - Alfiyana, Nadiyah (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
In this study, I will outline the strategy Emma Heesters employed as she attempted to translate Rizki Febian’s song Cuek into Ignore’s lyrics, regardless of whether she adopted a translation strategy that concentrated on the source or destination language. This essay also seeks to investigate the justification for the translation method. For this work, the author used a case study design and a qualitative research approach. The original and Emma Heesters’ translation of the lyrics to a Cuek song served as the study’s participants. The song lyrics were collected in both their English and Indonesian versions by the author using a documented technique to get the data. The author used Newmark’s theory to examine the data. The findings of this study show that, despite some song lyrics emphasizing the source language, the translation technique mostly concentrated on the target language. Therefore, the necessity to harmonize the translation’s intonation or tone with the music could account for Emma Heesters’ predisposition to stress the target language when translating. The fact that some lyrics were rewritten to better suit the female singer, whereas the original version was performed by a male singer, also played a role in this.